DISTRIBUTION AND GROWTH OF PINUS PUMILA REGEL ALONG THE LARIX GMELINII (RUPR.) RUPR. TIMBERLINE ECOTONE OF MT. DAL'NYAYA PLOSKAYA, CENTRAL KAMCHATKA (19th Symposium on Polar Biology) - オキツ, ススム; OKITSU, Susumu (National Institute of Polar Research, 1998)
P(論文) Variation in distribution and growth of Pmus pumila REGEL was described along a timberhne ecotone of Larix gmelimi (RUPR.) RUPR. from the closed forest margin (910 m altitude) up to the last trees of L. gmelinu (960 m altitude) on the western slope of Mt. Dal'nyaya Ploskaya, central Kamchatka. P pumila occurs exclusively within the range of L gmelmn; it never appears in a closed forest below the timberhne ecotone, and stopped at ca 100 m before the last trees of L. gmelinu in the upper part of the ecotone The mean annual stem elongation of P. pumila maintains constant value (around 5 cm/yr) at a stand along the ecotone under the protection of L. gmelmn trees providing wind-shelter, ameliorated temperature extremes and higher humidity. The distribution and growth pattern of P pumila suggest that P. pumila is ecologically one of an undergrowth element of L. gmelmn forests. Among the distribution areas of P. pumila, it can make its own vegetational zone only in restricted regions with peculiar environments where the thermal regime alone potentially permits arborescent trees to establish a forest, but in practice strong wind, snow and the exposure of a rocky substrate prohibit them from forming a forest zone. Such regions include high mountains of Japan and some mountains in Far East Russia. departmental bulletin paper